TANGGAPAN PENGUNJUNG TERHADAP DAYA TARIK MASJID SYAHBUDDIN DI KABUPATEN SIAK - Sintia Tri Anggriani; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Respon in the world of tourism is the opinion of way of view of visitorsand tourists in understanding a tourist destination. This research was conducted inSyahbuddin Mousque, Rempak Village, Siak District.This study aims to determinethe response of visitors to the attracition of Syahbuddin mousque. This researchuses quantitative descriptive method to process the data obtained in the fieldthrough interviews, observations and questionnaires. all the information collectedand studied to become a unified whole (Sugono 2000). As for the sample in research60 respondent. The determinantion of respondents with accidental sampling. Datacollection techniques used are observations, interviews, questionnaires, usingLikert scale as a measuring tool. Based on the results of research that has beendone the attracition of Syahbuddin mousque with sub variable arsitecture andFasility with good research conclusions.Keywords :Respon of visitors,Attraction, Mousque